Chanticleer and the fox - Chaucer, Geoffrey, -1400.; Cooney, Barbara, 1917-2000. (New York : HarperCollins, 1986)
A sly fox tries to outwit a proud rooster through the use of flattery.
"Adaptation of the 'Nun's priest's tale' from the Canterbury tales"--T.p. verso.
Keywords: Animals -- Fiction; Caldecott Medal; Fables